The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1600-051x.2009.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periodontitis and the causes of preterm birth: the case–control Epipap study

Abstract: Maternal periodontitis is associated with an increased risk of induced preterm birth due to pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 44 publications
2
80
0
11
Order By: Relevance
“…However, other cohort studies (36,(39)(40)(41), as well as case-control studies (17,(42)(43)(44)(45), did not find a significant association.…”
Section: Discussionmentioning
confidence: 80%
“…However, other cohort studies (36,(39)(40)(41), as well as case-control studies (17,(42)(43)(44)(45), did not find a significant association.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, several studies of periodontal disease in pregnancy have found that women with this condition have increased risks of intrauterine infections and preterm birth (Offenbacher et al 1996;Hill 1998;Jeffcoat, Geurs, Reddy, Cliver et al 2001;Khader and Ta'ani 2005;Nabet et al 2010;Riche et al 2002;Pizzo et al 2005). Interestingly, both live bacteria and bacterial products such as lipopolysaccharide can be found in the bloodstream of persons with periodontal disease following eating, routine oral hygiene and other periodontal procedures (Geerts et al 2002;Maestre et al 2008;Olsen 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that periodontal disease is associated with premature birth and low birth weight of babies 16,17 . However, other studies have pointed out the absence of these associations 18,19 .…”
Section: Discussionmentioning
confidence: 99%